Analisis Decline Curve Analysis (DCA) pada Reservoir Tight Gas Menggunakan Model Hyperbolic dengan Nilai b Mendekati Satu untuk Estimasi Cadangan Gas - Rizky, Muhammad; Rahman, Muhammad Rizqie Fathan; Rivani, Mukhlis Farhan (LPPM Universitas Pahlawan Tuanku Tambusai, 2026)
Gas reserve estimation is a critical aspect of field development planning, particularly for Tight Gas reservoirs characterized by low permeability and complex production decline patterns. This study aims to analyze gas production rate decline using the Decline Curve Analysis (DCA) method based on secondary production data from Mazher Ibrahim, processed using Microsoft Excel. The methods used include Exponential, Hyperbolic, and Harmonic models with a curve-fitting approach to determine the parameters qi, D, and b. The analysis results show that the Hyperbolic model with a value of b = 0.99 provides the best fit with the highest R² value and is capable of representing a rapid production decline pattern at the beginning that flattens over time. Based on this model, an estimated recoverable reserves (EUR) of 2,065 MMSCF was obtained, with a predicted production life of approximately 23 years. The DCA method is recommended as a simple and effective approach for evaluating Tight Gas reservoirs.